2020
DOI: 10.1038/s41598-020-58040-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenome-wide functional dissection of pleiotropic effects highlights key molecular pathways for human complex traits

Abstract: Over the recent decades, genome-wide association studies (GWAS) have dramatically changed the understanding of human genetics. A recent genetic data release by UK Biobank (UKB) has allowed many researchers worldwide to have comprehensive look into the genetic architecture of thousands of human phenotypes. In this study, we used GWAS summary statistics derived from the UKB cohort to investigate functional mechanisms of pleiotropic effects across the human phenome. We find that highly pleiotropic variants often … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 44 publications
5
54
1
Order By: Relevance
“…Results from just over a decade of genome-wide association studies (GWAS) have demonstrated that statistical pleiotropy across the genome is ubiquitous, meaning that particular genetic variants, genes, or genomic regions often show association with more than one trait 13 . Pleiotropy is valuable to study for a number of reasons, as it could elucidate biological pathways that are shared between traits 46 , help generate hypotheses about the functional significance of GWAS results 79 , and improve our understanding of the aetiology and overlap between complex traits and diseases 1,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Results from just over a decade of genome-wide association studies (GWAS) have demonstrated that statistical pleiotropy across the genome is ubiquitous, meaning that particular genetic variants, genes, or genomic regions often show association with more than one trait 13 . Pleiotropy is valuable to study for a number of reasons, as it could elucidate biological pathways that are shared between traits 46 , help generate hypotheses about the functional significance of GWAS results 79 , and improve our understanding of the aetiology and overlap between complex traits and diseases 1,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Here we carried out an analysis of variants recovered from the GWAS Catalog for 41 human traits and diseases to investigate the mean frequency, effect size, recombination rate and intensity of background selection associated with variants with different degrees of pleiotropy. In addition, we investigated the intensity of background selection associated with the data sets of pleiotropic variants analyzed by Pickrell et al (2016), Watanabe et al (2019) and Shikov et al (2020). Overall, the results suggest that more pleiotropic variants are located in regions with stronger background selection.…”
Section: Introductionmentioning
confidence: 97%
“…Wang et al 2010;Sivakumaran et al 2011;Pickrell et al 2016;Chesmore et al 2018;Jordan et al 2019;Watanabe et al 2019;Shikov et al 2020) and it has been suggested that complex traits are driven by an enormously large numbers of genes, implying that pleiotropy is the rule rather than the exception (Boyle et al 2017). The latest meta-analysis on pleiotropic variants carried out by Shikov et al (2020), and based on more than five hundred complex traits, concludes that about 180 Mbs of the human genome are covered by pleiotropic loci and about 50% of SNPs are associated with more than one phenotype. Another recent study (Watanabe et al 2019) suggests that this proportion is even larger (60 %).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations